Resource Sharing in Academic Libraries - Parvin, Begam (International Journal of Research in Interdisciplinary Studies, 2025)
Libraries are the learning centres but in the present information age it is quite impossible to any library to be remaining self reliant. So the resource sharing is very much essential to overcome this situation. Sharing of resources means sharing one’s assets or library materials with another libraries. Now some consortia have started functioning for resource sharing. These consortia have started sharing of e-journals. This will ensure maximum saving with regard to money spent on acquisition of information resources throughout the country and will help in research at all levels thereby contributing greatly in national development.